Robotic Leg Design to Analysis the Human Leg Swing from Motion Capture - Riky Tri Yunardi; Aji Akbar Firdaus; Eva Inaiyah Agustin (Institute of Advanced Engineering and Science, 2017)
In this paper presented the prototype of robotic leg has been designed, constructed and controlled. These prototype are designed from a geometric of human leg model with three joints moving in 2D plane. Robot has three degree of freedom using DC servo motor as a joint actuators: hip, knee and ankle. The mechanical leg constructed using aluminum alloy and acrylic material. The control movement of this system is based on motion capture data stored on a personal computer. The motions are recorded with a camera by use of a marker-based to track movement of human leg. Propose of this paper is design of robotic leg to present the analysis of motion of the human leg swing and to testing the system ability to create the movement from motion capture. The results of this study show that the design of robotic leg was capable for practical use of the human leg motion analysis. The accuracy of orientation angles of joints shows the average error on hip is 1.46º, knee is 1.66º, and ankle is 0.46º. In this research suggesting that the construction of mechanic is an important role in the stabilization of the movement sequence.